2003
DOI: 10.1099/jmm.0.04935-0
|View full text |Cite
|
Sign up to set email alerts
|

Production by Bacillus pumilus (MSH) of an antifungal compound that is active against Mucoraceae and Aspergillus species: preliminary report

Abstract: A compound produced by Bacillus pumilus (MSH) that inhibits Mucoraceae and Aspergillus species is described. Fungicidal activity was demonstrated by lawn-spotting and by diffusion through 0·45 ìm Millipore membranes placed on 5 % sheep-blood agar, nutrient agar, trypticase soy agar and Mueller-Hinton agar, followed by spore inoculation of the bacterium-free underlying agar surface. With either technique, zones of fungal inhibition correlated with the zone of haemolysis produced by B. pumilus (MSH). The active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 12 publications
4
46
0
Order By: Relevance
“…This is in agreement with bibliographical data showing that Bacillus produces antimicrobial substances of protein nature (Wu et al, 2005). These molecules are essentially active against Gram-positive bacteria, nevertheless compounds such as polymixin and colistin inhibit Gram-negative forms (Bottone and Peluso, 2003), whereas Bacillomycin, Mycobacillin, and Fungistatin are active against yeasts and fungi (Katz and Demain, 1977). Bottone and Peluso (2003) have reported the inhibition of species from the genera Mucoraceae and Aspergillus by an antifungal compound produced by B. pumilus.…”
Section: Microorganismsupporting
confidence: 76%
“…This is in agreement with bibliographical data showing that Bacillus produces antimicrobial substances of protein nature (Wu et al, 2005). These molecules are essentially active against Gram-positive bacteria, nevertheless compounds such as polymixin and colistin inhibit Gram-negative forms (Bottone and Peluso, 2003), whereas Bacillomycin, Mycobacillin, and Fungistatin are active against yeasts and fungi (Katz and Demain, 1977). Bottone and Peluso (2003) have reported the inhibition of species from the genera Mucoraceae and Aspergillus by an antifungal compound produced by B. pumilus.…”
Section: Microorganismsupporting
confidence: 76%
“…[21] In the search for antibiotics produced by Bacillus species, especially Bacillus cereus, Bacillus subtilis and Bacillus licheniformis, several antifungal compounds, mainly peptides, have also been described. [22,23,24,25] Bottone & Peluso [26] have reported a compound produced by Bacillus pumilus (MSH) that inhibits…”
Section: Discussionmentioning
confidence: 99%
“…The exact size of the plasmid could only be ascertained on a pulse field gel electrophoresis since the resolution of agarose gel electrophoresis is ∼23 kb but the modified in situ plasmid isolation method too revealed the size of the plasmid to be equivalent to plasmid of E.coli S17, which is 23 kb. Biological & physiochemical characterization of Bacillus pumillus and its antifungal compounds have been described earlier [19] but presence of plasmid in Bacillus pumillus has not been reported so far. Bacillus pumillus MTCC7615 is resistant to antibiotic naldixic acid and it was observed that antibiotic naldixic acid resistance gene is associated with the plasmid pJCP07 of Bacillus pumillus MTCC7615 since curing the isolate of its plasmid pJCP07 made it naldixic acid-sensitive.…”
Section: Pcr Studies To Confirm Presence Of Tn5mentioning
confidence: 99%